OPTIMALISASI ADMINISTRASI GURU MELALUI PELATIHAN BERBASIS DESIGN THINKING DENGAN PLATFORM MERDEKA MENGAJAR - Ahdhianto, Erif; Barus , Yohannes Kurniawan; Mas'ula, Siti; Thohir , M. Anas; Cahyani, Fitriana Kurnia; Aprilia, Ariska Dwi (Universitas PGRI Yogyakarta, 2025)
This community service aims to enhance elementary school teachers’ ability to utilize the Merdeka Mengajar Platform (PMM) using the Design Thinking approach. The main issues addressed include a lack of understanding of PMM features and administrative challenges that hinder teaching processes. The implementation method follows the five stages of Design Thinking: Empathize, Define, Ideate, Prototype, and Test, designed to provide training based on the real needs of teachers. The results show that the training successfully improved participants' understanding of PMM, with an average satisfaction level of 4.8 on a Likert scale. Teachers also gained confidence in identifying problems and designing creative solutions. However, time constraints limited participants’ opportunities to explore the material deeply. The program recommends follow-up training, replication in other regions, and continuous assistance to support the implementation of technology in the field. Keyword: Administration, Design Thinking, Education, PMM, Technology